SCIENTIFIC PERSPECTIVE OF KNOWING GOD ACCORDING TO MUHAMMAD BIN ABDUL WAHHAB IN THE BOOK OF MATAN AL-USHUL ATS-TSALATSAH - Muslimah Muslimah; Humaydi Humaydi; Muhammad Muchtar Lubis (FORUM PAEDAGOGIK, 2022)
The wrong knowledge that a Muslim must know and learn is the science of monotheism, namely knowing Allah, this knowledge will save him in this world and the hereafter. The aim of the research is to analyze the perspective of knowledge of Allah according to Muhammad bin Abdul Wahhab in the book of Matan Al-Usul Ats-Tsalatsah. A qualitative approach with the type of research library research and analysis of discourse analysis techniques. The research findings that the knowledge of knowing Allah according to Muhammad bin Abdul Wahhab is knowing Allah is the Lord who must be worshiped carrying out orders and avoiding His prohibitions, and not associating partners with Allah by combining monotheism rububiyyah and uluhiyyah. How to God through His signs, namely the night, day, sun, and moon, and also through His creation namely the seven layers of heaven and seven layers of earth. Getting to know Alla by carrying out the acts of worship commanded by Him, namely prayer, Kauf, raja' (hope), trust, raghbah (interested), rahbah (anxious), solemn, khasyyah (fear), inabah (return to Allah), istianah, istiadzah, istigasah, slaughtering sacrificial animals, vows.